2022
DOI: 10.1371/journal.pone.0268129
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis of determinants of anemia among young women (15-24) in sub-Sahara Africa

Abstract: Background Anemia is a disorder by which the body’s red blood cells are inadequate to fulfill The physiological needs of the body. The World Health Organization (WHO) defines anemia as having a hemoglobin (Hb) level of less than 120 g/l for nonpregnant women and 110 g/l for pregnant women. It has serious implications for human health as well as negative social and economic consequences like decreased workforce, impaired learning, and stunted child development. As these women are highly vulnerable to different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
14
7
1
Order By: Relevance
“…This indicates reduced severity of anemia within the selected district populations. Median Hb concentrations were comparable to other studies conducted in the region; Togo and sub‐Saharan African countries (Nambiema et al, 2019; Worku et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…This indicates reduced severity of anemia within the selected district populations. Median Hb concentrations were comparable to other studies conducted in the region; Togo and sub‐Saharan African countries (Nambiema et al, 2019; Worku et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…Less than half of women (41.0%) were anemic. This result is somewhat consistent with a previous study that found the prevalence of anaemia to be 42.2% [ 14 ]. Concerning the covariates, the study revealed that compared to adolescents, older women (i.e., 20 years and older) were less likely to be anemic.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies [ 14 , 32 ], the current study found lower risk of anaemia among women who had formal education compared with those with no formal education. Formal education has been linked to good knowledge on nutritional and dietary needs as well as better uptake of healthcare services [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations